Seismic pounding simulation between Two adjacent Buildings - Bajracharya, Sanjeema; Pokharel, Uzwal; Katwal, Ujwal; Karki, Samir; Bajgain, Rajiv; Upadhaya, Umesh; Yadav, Subigya Kumar (Journal of Innovations in Engineering Education, 2025)
The seismic hazard of structures colliding during an earthquake, arising from constrained separation gaps between adjacent buildings, constitutes a significant concern. This phenomenon is particularly pronounced in seismically active region like Kathmandu with dense plinth to land space ratio. Such scenarios result in heightened risks of collisions, increased building displacements with instantaneous acceleration, and greater ductility demands. This research delves into the impact of pounding on adjacent Reinforced Concrete (RCC) buildings aligned and symmetric on plan. The focus is specifically on two neighboring buildings with different storey heights but same floor heights, also designing them using relevant IS codes. The investigation also explores the influence of the initial separation gap between the interacting structures on pounding force. The building models are constructed using ETABS software, and time history analysis is employed for the evaluation and spectral matching is done with SeismoMatch2025. The findings, covering pounding force, joint acceleration before and after pounding are presented and analyzed. The seismic gap provided as per IS 1893: 2016 is sufficient to control seismic pounding and insufficient gap leads to more pounding than no seismic gap.